Java programming for complete beginners. (Packt Publishing, 2022)
A course that will teach you every topic and concept of Java programming in detail, which will help you boost your coding skills. About This Video Learn the core Java skills needed to start your career as a Java developer Create multiple short projects along the way to gain confidence Learn industry best practices in Java software development from a professional Java developer In Detail Java programming language is very powerful and scalable and is used to create different software applications. The main reason many companies use Java is its popularity and usage in the industry. According to many official websites that track the popularity of languages, Java is either #1 or in the top 3. So, that means more companies and their staff are using it, so there are more career opportunities available for you if you are skilled in the language. You will start by understanding all the core OOPS concepts, what polymorphism and inheritance is, and apply them to your application. You will also learn all the essential Java keywords, operators, statements, loops, and expressions. You will understand how to download and install all the necessary coding tools and learn to perform code refactoring. Along the course, you will learn how to use different packages available. You will learn the concepts and usage of multithreading. Learn how to analyze logs and explore Java debugging techniques such as stack trace and breakpoints. You will also learn how to use the JUnit framework and implement Java design patterns. By the end of this course, you will have understood the building blocks of Java programming language. Audience This course is for software developers and programming enthusiasts. It is ideal for absolute beginners with no previous coding experience, for intermediates looking to sharpen their skills, for those who are looking to start/switch their career in Java, and for those looking to build a career in Big Data as Java is used in a lot of technologies.